Delivering climate change outcomes with agroecology in low- and middle-income countries: evidence and actions needed - Snapp, Sieglinde S.; Kebede, Yodit; Wollenberg, Eva Karoline; Dittmer, Kyle; Brickman, Sarah; Egler, Cecelia; Shelton, Sadie W. (Center for Development Research (ZEF) in cooperation with the Scientific Group for the UN Food System Summit 2021, 2021)
Food systems need to meet food security, nutrition and environmental goals, especially in a world with growing demand and a changing climate. There is now broad consensus on the need to transform current food systems towards more sustainable models. Agroecology is increasingly seen as a framework to transform food systems. A key question is: how far can agroecology meet the needs for climate change adaptation and mitigation in the food system, especially in low- and middle-income countries (LMICs) and at large scales? To address this question, we conducted a rapid evidence-based review to assess the quality and strength of evidence regarding (i) the impact of agroecological approaches on climate change mitigation and adaptation in LMICs, and (ii) the programming approaches and conditions supporting large-scale transitions to agroecology.